Application Of The Least Square Method For Website Based Shrimp Sales Prediction - Muhsina, Muhsina; Siska Anraeni; Muhammad Arfah Asis (Yayasan Insan Mulia Bima, 2024)
UD Arif is a company engaged in the business of buying and selling shrimp, this company is located on Jalan Soreang No.127 Pitue, Desa Pitue, Kec. Ma'rang, Kab.Pangkep. The problem that is often experienced at UD Arif is the amount of shrimp availability that does not match customer demand because shrimp quickly deteriorate and sales fluctuate due to market demand, such as the size of the shrimp that must be stocked, the quality of the shrimp, and too much stock on the market resulting in Shrimp sales decline Therefore the aim of this study is to produce an application that can make UD Arif's youth easier in predicting shrimp sales. So the method used in this study is the least squares method, which is a method that can handle data that experiences ups and downs, where it is influenced by seasons and trends. The result of this research is to produce a website that can predict shrimp sales. These results are known by means of correlation, namely looking for a relationship between the original data and the predicted data calculated using Excel. From this correlation method, it is known that with 12 months of test data, it is possible to have a vannamei shrimp test with a MAPE result of 3.7%.